Dietary ferulic acid supplementation improved cottonseed meal-based diet utilization by enhancing intestinal physical barrier function and liver antioxidant capacity in grass carp (Ctenopharyngodon Idellus) - Chen, Shiyou; Lin, Yan; Shi, Hequn; Miao, Linghong; Liu, Bo; Ge, Xianping (Frontiers in Physiology, 2022)
The present study explored the effects of ferulic acid (FA) supplementation in cottonseed meal (CSM)-based diets on grass carp growth performance, feed utilization, liver antioxidation status, and intestinal physical barrier function. Here, four experimental diets supplemented with FA at graded levels (0, 50, 100 and 200 mg/kg) and CSM as the main protein source (384.6 g/kg feed) for an 8-week feeding trial. Our results indicated that 200 mg/kg FA supplementation in a CSM-based diet significantly improved growth performance [including final body weight (FBW), weight gain rate, and specific growth rate] and feed utilization [including feed conversion ratio and protein efficiency ratio] in grass carp (p < 0.05). The results of polynomial regression analysis based on FBW recommended that the optimal dose for FA supplementation was 204 mg/kg. Compared with that no FA supplementation, 200 mg/kg FA supplementation significantly reduced liver malondialdehyde levels and increased glutathione reductase activities (p < 0.05) and 100 mg/kg FA supplementation significantly increased liver total superoxide dismutase activities and reduced blood alanine transaminase levels (p < 0.05). Compared with the control group, 100 mg/kg FA supplementation also led to significantly increased mRNA expression of zo-1, zo-2, occludin, claudin-b, claudin-3, claudin-7a, and claudin-12, encoding intestinal tight junction proteins (p < 0.05). Notably, FA supplementation could reduce lipid deposition by regulating bile acid (BA) secretion. In this study, 100 and 200 mg/kg FA supplementation significantly increased blood and liver total BA levels, respectively (p < 0.05); 100 mg/kg FA also significantly activated mRNA expressions of fxr and cyp7a1 (p < 0.05). Furthermore, the whole-body composition results presented that FA treatment relieved lipid deposition, particularly 50 and 200 mg/kg FA supplementation (p < 0.05). Moreover, triglyceride and total cholesterol levels were significantly lower and high-density lipoprotein levels were significantly higher with 200 mg/kg FA supplementation than with no FA supplementation (p < 0.05). Taken together, the results indicated that FA may be a beneficial feed additive to boost fish growth performance and increase CSM utilization.